2019
DOI: 10.2459/jcm.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar active fixation left ventricular lead or quadripolar passive fixation lead? An Italian multicenter experience

Abstract: Aims About one-third of patients receiving cardiac resynchronization therapy (CRT) are not responders, due to either patient selection or technical issues. Left ventricular quadripolar passive fixation leads (QPL) and bipolar active fixation (BAF) leads have been designed to ensure a targeted left ventricular stimulation area, minimizing lead dislodgments and phrenic nerve stimulation (PNS). The aim was to compare real-world safety and efficacy of BAF (Attain Stability, Medtronic Plc.) and QPL (Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 25 publications
2
17
1
Order By: Relevance
“…Our results are at face value different from those from a previous study comparing bipolar active fixation leads and quadripolar passive leads which found no difference in lead dislodgements 10 . The latter though was based on macrodisplacements and in the current study, we looked at a combination of microdisplacements along with displacements requiring intervention, giving a far more sensitive assessment.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…Our results are at face value different from those from a previous study comparing bipolar active fixation leads and quadripolar passive leads which found no difference in lead dislodgements 10 . The latter though was based on macrodisplacements and in the current study, we looked at a combination of microdisplacements along with displacements requiring intervention, giving a far more sensitive assessment.…”
Section: Discussioncontrasting
confidence: 91%
“…[7][8][9] A recent retrospective study compared 261 bipolar AS leads with 124 passive quadripolar leads and showed no difference in total displacements between active and passive leads. 10 The lead has also been extracted without incident up to 18 months postimplant. [10][11][12] In view of the novel nonwedged, more proximal active fixation deployment necessitated by the lead, in this study we sought to compare the electromechanical stability of AS with passive fixation CS leads.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal long-axis LV lead position is debatable, and the future may show that the optimal long axis position occurs on an individual basis. A nonrandomized multicenter trial that compared active fixation LV leads with quadripolar LV leadsreported noninferior clinical outcomes for the active fixation leads 16.…”
mentioning
confidence: 99%